Thalamocortical input onto layer 5 pyramidal neurons measured using quantitative large-scale array tomography - Rah, Jong-Cheol; Bas, Erhan; Colonell, Jennifer; Mishchenko, Yuriy; Karsh, Bill; Fetter, Richard D.; Myers, Eugene W.; Chklovskii, Dmitri B.; Svoboda, Karel; Harris, Timothy D.; Isaac, John T. (Frontiers in Neural Circuits, 2013)
The subcellular locations of synapses on pyramidal neurons strongly influences dendritic integration and synaptic plasticity. Despite this, there is little quantitative data on spatial distributions of specific types of synaptic input. Here we use array tomography (AT), a high-resolution optical microscopy method, to examine thalamocortical (TC) input onto layer 5 pyramidal neurons. We first verified the ability of AT to identify synapses using parallel electron microscopic analysis of TC synapses in layer 4. We then use large-scale AT to measure TC synapse distribution on L5 pyramdial neurons in a 1.00 x 0.83 x 0.21 mm^3 volume of mouse somatosensory cortex. We found that TC synapses primarily target basal dendrites in layer 5, but also make a considerable input to proximal apical dendrites in L4, consistent with previous work. Our analysis further suggests that TC inputs are biased towards certain branches and, within branches, synapses show significant clustering with an excess of TC synapse nearest neighbors within 5-15 μm compared to a random distribution. Thus, we show that AT is a sensitive and quantitative method to map specific types of synaptic input on the dendrites of entire neurons. We anticipate that this technique will be of wide utility for mapping functionally-relevant anatomical connectivity in neural circuits.